Effect of Core Stability Exercise in Preventing Diastasis Recti Abdominis among Normal Birth Delivery of Postpartum Mothers: Meta-Analysis - Oktaviyani, Feny; Pamungkasari, Eti Poncorini; Murti, Bhisma (Indonesian Journal of Medicine, 2022)
Background: Diastasis Recti Abdominis (DRA) is a separation that occurs in the abdominal muscles, namely between the two rectus abdominis muscles. This separation is precisely in the linea alba which is the midline of the abdomen. DRA is characterized by two things, namely the widening of the inter-recti distance (IRD) and the appearance of a bulge in the abdomen. This is due to stretching and weakness of the linea alba. This study aims to analyze the effect of core stability exercise on reducing diastasis recti abdominis in normal postpartum mothers based on the results of a number of previous primary studies.Subjects and Method: This study uses a meta-analysis method with articles searched using the search keywords "Core stability exercise" AND "diastasis recti abdominis" OR "normal post partum" OR "caliper" OR "ultrasonography" OR "Randomized Controlled Trial" OR "RCT" from PubMed, Google Scholar and Scopus and processed using RevMan 5.3.Results: 9 RCT articles that fit into the inclusion criteria, with a total of 319 samples. Normal postpartum mothers with diastasis recti abdominis who received core stability exercise had an average caliper score of 4.71 units lower than those without core stability exercise, and the effect was statistically significant (SMD= -4.71; 95% CI -8.05 to -1.37; p= 0.060). Normal postpartum mothers with diastasis recti abdominis who received core stability exercise had an average ultrasound score of 0.80 units lower than those without core stability exercise, and the effect was statistically significant (SMD= -0.80; 95% CI -1.62 to 0.02; p= 0.060). In other words, core stability exercise is effective in reducing diastasis recti abdominis in normal postpartum mothers.Conclusion: Core stability exercise has an effect on reducing diastasis recti abdominis in mothers after normal delivery.Keywords: post partum, diastasis recti abdominis, core stability exercise, calipers, ultrasoundCorrespondence: Feny Oktaviyani. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: fenyokta89@gmail.com. Mobile: +6281312500575.Indonesian Journal of Medicine (2022), 07(02): 188-199https://doi.org/10.26911/theijmed.2022.07.02.07